Australian Sports Drug Agency
Australians are renowned for their sporting prowess and sense of fair play ... so in 1990, responding to public concerns about the use of drugs in sport, the Australian Government established the Australian Sports Drug Agency. The agency's primary and most significant role is to conduct a comprehensive drug testing program. Our aim: deterring elite athletes from taking prohibited substances. We work in partnership with sports organisations at the state, national and international level to develop a comprehensive response to drugs in sport issues. The Australian Sports Drug Agency is a Commonwealth statutory agency within the Industry, Science and Tourism Portfolio. It was established by the Australian Sports Drug Agency Act 1990 (ASDA Act). Amendments were made to the Act in 199192, 199293, 199394, 199495 and 199697. The Australian Sports Drug Agency Amendment Bill 1996 received Royal Assent on 28 June 1996. Organisational structure - Overview Legislative basis Minister responsible Board members Contact information Changes to ASDA's Legislation Purpose of the changes Greater flexibility Streamline result management procedure Enhance Assessment of Positive Test Results, Provide Expert Scientific/Medical Information to Sports Doping Tribunals and Approve Use of Banned Substances for Therapeutic Purpose Ancillory sports drug testing services State and Territory sports drug testing legislation Receiving information from the Australian Customs Service Accessing ASDA Legislation Drugs in sport (Infopac) History of drug use in sport. Why do athletes use drugs? Performance enhancing substances. International Olympic Committee Medical Code - Classes of prohibited substances and methods in doping Banned substances and methods Restricted substances Vitamins and supplements Drug Testing: An Athletes Guide The Australian Sports Drug Agency The drug testing process Drug testing 1 Selection 2 Notification 3 Presenting for a drug test 4 Providing a sample Athletes with disabilities 5 Choosing your secure containers 6 Splitting, sealing and labelling your sample 7 Checking pH and concentration of sample 8 Final paperwork Security of your sample Analysis procedure Athlete's rights and responsibilities Your rights Positive test results process Your responsibilities Sanctions Substances and methods tested for Prohibited substances Prohibited methods Before you take any medication Can't find it in the Drugs in Sport Handbook? Further information on the drugs banned by your sport Publications & Resources Drugs in Sport Handbook and Wallet Card Drug Testing Video Postage & Handling Trends in drug testing Drug testing statistics: Quarter ending 30 September 1999 Entries on the International List of Incidences 1998-99 total drug testing numbers Summary of government-funded and user-pays drug testing by sport Government-funded testing 1998-99 User-pays testing 1998-99 Entries on Register of Notifiable Events for 1998-99 by class and substance Entries on Register of Notifiable Events from previous years where outcomes were to be advised Media releases and briefings ASDA goes hi-tech to increase drug testing and information services More drug tests planned in lead up to Sydney 2000 ASDA to conduct unprecedented drug tests prior to Sydney 2000 Anabolic agents dominate drug testing results Newsletters Newsletters Main Menu Drugs in Sport Update (Vol 3, Issue 3) Spring 1999 edition Drugs in Sport Update (Vol 3, Issue 2) Winter 1999 edition Drugs in Sport Update (Vol 3, Issue 1) Autumn 1999 edition Drugs in Sport Update (Vol 2, Issue 3) Spring 1998 edition Links